Evidence of seropersistent VDRL test reactivity in an elderly Treponema pallidum-infected population - Muić, Vladimir (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2000)
Background. Using the VDRL test as the only one, or the first in a series of tests, leads to a diagnostic miss in the serological detection of latent and late syphilis, especially among older age group. We compared the age of 518 Treponema pallidum-infected individuals with their VDRL test results. This wasaimed at determining the proportion of VDRL reactors who were suspected of having a persistently active syphilitic process. Methods. Our retrospective analysis of archival data on subjects' age and VDRL serotest outcomes for the 518 Treponema pallidum-infected (who were reactors in the TPHA reference test)covered the period 1974-98. They were selected from a nonvenerological population routinely tested at a public health laboratory. Results. Data analysis revealed the subjects' high mean age (53.13 years in VDRL reactors and 51.87 years in nonreactors), and an unexpectedly high proportion of VDRL reactors (49%) among those tested. Conclusion. It may be presumed based on the49% persistence of VDRL reactivity coupled with the subjects' high mean age(53.15 years), which is appropriate to latent and late syphilis, that most subjects (70%) had either been untreated or insufficiently treated. This view is based on the Bayes' theorem, which takes account of the generally accepted percentage of VDRL reactivity for latent and late syphilis.
Keywords: Aged; Croatia; diagnostika; sifilis; spolne bolezni; Syphilis serodiagnosis; Syphilis, latent; Treponema pallidum